Data acquisition and management of wind farm using edge computing. (14th July 2022) - Cao, Xin; Xu, Yifei; Wu, Zhiwei; Qin, Xiaoliang; Ye, Fang
The purpose is to deal with the increasingly serious energy crisis and prominent environmental problems in recent years, collect and manage the power data of wind farms and ensure the normal transmission of data information in the wide weak signal coverage area of the wind farm. First, the principle and advantages of edge computing technology are described. Then, the application of this technology to the data acquisition system of wind farms is proposed, making the data acquisition and management work normally. Finally, the application of edge computing technology in wind farm data acquisition and management is simulated, and the results are compared. The results show that the application of edge computing in wind farm data acquisition and management can improve the difficulties of data information transmission caused by the geographical situation and weak signal coverage of wind farms. Moreover, using edge computing technology makes data acquisition and management more efficient and accurate. This exploration provides a new direction for the application of emerging computer technology in the power Internet of Things (IoT) system, and sets an example for future related research.